PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWTOON PADA POKOK BAHASAN KOLOID DI SMA/MA - Wisnarni J, Elvie; Haryati, Sri; ', Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is aimed to develop learning media by using PowToon on the subject of Colloid at SMA/MA. The result of this study is a product of learning media in the form of CD (compact disk) for Colloid subject which has contents as follows: colloids system, the characteristics of colloids, the role colloids in life and manufactured of colloidal. This study used Research and Development (R&D) method with ADDIE model which has five stages of development; they are analysis, design, development, implementation, and evaluation. The development model was modified by the writer only until the development stage. The result of validation test showed that learning media on the subject of Colloid is valid with the result of validation by media experts and material experts 91,14%, so the developed learning media is properly used on the learning and teaching process. The result of the development has been limited test on 15 students and average score percentase obtained by 86,13%.Key Words : Development of learning media, PowToon, Colloid